Pregnancy diagnosed in a rudimentary horn of uterus: a rare case report - Bhatt, Jalpa K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Pregnancy in a rudimentary horn of the uterus is a quite rare clinical condition with a reported incidence of 1 in 100,000 to 140,000 pregnancies. The patient may get complicated if not diagnosed timely. The standard treatment is the surgical excision of the horn. A gravida 1, para 0 patient presented at 5 weeks gestation diagnosed as pregnancy in rudimentary horn. She underwent a laparotomy with right rudimentary horn excision. The final diagnosis of pregnancy in rudimentary horn was confirmed by histopathology. A unicornuate uterus with a rudimentary horn is a congenital uterine anomaly resulting from the incomplete development of one of the Müllerian ducts also incomplete fusion with the contralateral side. This case highlights the importance of an early detection by ultrasound and the need for high clinical diagnosis with suspicion.